Uganda’s access to the European Union agricultural market: Challenges and opportunities - Mugyenyi, Onesmus; Naluwairo, Ronald (Advocates Coalition for Development and Environment ACODE, 2003)
The last three decades of trade between Uganda and European Union have not benefited Uganda. Generally the annual trade balance has been negative raising the level of Uganda's external debt to US$ 3.68 billion as of June ,2000. The Lomé Trading arrangement (1975-2000) has not been able to change the trend due to a number of challenges. The Cotonou Partnership Agreement and the EBA initiative may not be able to change the trend unless these challenges have been addressed. The major constraints have been internal, external and structural. The internal factors range from poor trade policies, inadequate support to private sector, narrow export base, reliance on export of raw materials and high level corruption. The external factors include non-tariff barriers, protectionist policies, subsidies, tariff peaks and escalation. The structural challenges mainly relate to poor infrastructure, poor product quality, poor and obsolete technology, poor marketing techniques and insufficient market knowledge which can be summarized as supply side constraints.